Die Fremdsprache Deutsch als Unterrichtssprache im DaF-Unterricht – das Fallbeispiel Polen - Badstübner-Kizik, Camilla; Bielicka, Małgorzata (Neofilolog, 2023)
The first step in acquiring a language is to extract information from the environment. The research conducted in this field mainly focuses on two aspects: the role of language input as a trigger for language acquisition processes and the corrective function of language. The paper discusses classroom language as one of the most important sources of language input in foreign language teaching, whereby special attention is given to the quality and quantity of language input provided by Polish teachers of German as a foreign language. After presenting an overview of relevant research findings, recommendations for the use of foreign language in classroom communication are given, with reference to the example of German as a foreign language.